2017
DOI: 10.1128/aac.00165-17
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Homoserine Dehydrogenase of Paracoccidioides Species for Treatment of Systemic Fungal Infections

Abstract: This work evaluated new potential inhibitors of the enzyme homoserine dehydrogenase (HSD) of Paracoccidioides brasiliensis, one of the etiological agents of paracoccidioidomycosis. The tertiary structure of the protein bonded to the analogue NAD, and L-homoserine was modeled by homology. The model with the best output was subjected to gradient minimization, redocking, and molecular dynamics simulation. Virtual screening simulations with 187,841 molecules purchasable from the Zinc database were performed. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…Rational drug design involves the use of computational tools in drug discovery as a cost-effective alternative to traditional experimental protocols [41]. Several research groups have shown the excellent antifungal potential of compounds selected by virtual screening of small molecule libraries against specific targets [26,39,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Rational drug design involves the use of computational tools in drug discovery as a cost-effective alternative to traditional experimental protocols [41]. Several research groups have shown the excellent antifungal potential of compounds selected by virtual screening of small molecule libraries against specific targets [26,39,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…This work reports the antifungal effects of these two oxadiazoles against Paracoccidioides spp., presenting an inhibition profile with MIC values between 1 and 32 μg/mL. Several studies have used the in silico approach to identify compounds for PCM treatment [16, 20, 25, 30, 35, 37]. The MIC values for these compounds was always similar to oxadiazoles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two homoserine dehydrogenase inhibitors demonstrated antifungal activity (MIC values 32–64 μg/mL) [25]. This group also synthetized 4-methoxy-naphthalene derivatives with antifungal activity against Paracoccidioides spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 3 thioredoxin reductase inhibitors were selected by virtual screening with antifungal activity against Paracoccidioides spp., with MICs of 8 to 32 mg/liter (28). Furthermore, two compounds (HS1 and HS2) have been identified as homoserine dehydrogenase inhibitors showing antifungal activity (32 to 64 mg/liter) against P. brasiliensis (29). A Brazilian medicinal plant called Schinus terebinthifolius presented inhibitory activity against isolates Pb18 and Pb01, with MICs of 62.5 to 250 mg/liter (30).…”
Section: Discussionmentioning
confidence: 99%